Exploring the antecedents of learning-related emotions and their relations with achievement outcomes - Alexandra Corina Niculescu; Dirk Tempelaar; Amber Dailey-Hebert; Mien Segers; Wim Gijselaers (EARLI, 2015)
Recent work suggests that learning-related emotions (LREs) play a crucial role in performance especially in the first year of university, a period of transition for most students; however, additional research is needed to show how these emotions emerge. We developed a framework which links a course-contextualized antecedent - academic control in Pekrun's (2006) Control Value Theory of Achievement Emotions - with generic antecedents - adaptive and maladaptive cognitions and behaviors from Martin's (2007) Motivation and Engagement Wheel framework - to explain a classical problem: the emergence of LREs in a transition period. Using a large sample (N = 3451) of first year university students, our study explores these two antecedents to better understand how four LREs (enjoyment, anxiety, boredom and hopelessness) emerge in a mathematics and statistics course. Through the use of path-modelling, we found that academic control has a strong effect on all four LREs - with the strongest impact observed for learning hopelessness and secondary, for learning anxiety. Academic control, on its turn, builds on contributions from adaptive and mal-adaptive cognitions. Furthermore, adaptive cognitions have an impact on learning enjoyment (positive) and on boredom (negative). Surprisingly though, the maladaptive behaviors impact positively learning enjoyment and negatively learning anxiety. Following this, we predicted performance outcomes in the course and found again academic control as the main predictor, followed by learning hopelessness. Overall, this study brings evidence that adaptive and maladaptive cognitions and behaviours act as important antecedents of academic control, the main predictor of LREs and course performance outcomes.